Application of Green Chemical Synthesis Technology in Fragrance Industry - Yang Chen (MATEC Web of Conferences, 2025)
Fragrance compounds are indispensable in various industries and daily applications, including food, cosmetics, and pharmaceuticals. Traditional synthesis methods, however, often rely on chemical reagents under harsh conditions, such as high temperatures and pressures, leading to significant environmental pollution and resource inefficiency. Green chemistry, as a transformative approach, offers sustainable alternatives for fragrance synthesis by utilizing renewable feedstocks, efficient catalysts, and environmentally benign solvents. This work systematically explores recent advancements in green synthesis technologies for fragrances, focusing on three core areas, biocatalysis, innovative catalysts, and green solvents. Biocatalysis has achieved remarkable progress in enhancing reaction selectivity and reducing energy consumption, while novel catalysts demonstrate potential for improving atom economy and minimizing by- product formation. Furthermore, green solvents present promising solutions to replace conventional organic solvents, significantly reducing environmental impact. By analysing the technical advantages and future prospects of these strategies, a comprehensive framework is provided to support the sustainable transformation of the fragrance industry, promoting its shift toward a greener and more resource-efficient paradigm.